2007
DOI: 10.1557/jmr.2007.0308
|View full text |Cite
|
Sign up to set email alerts
|

A simple route for manufacturing highly dispersed silver nanoparticles

Abstract: Highly dispersed uniform silver nanoparticles were prepared by reducing silver diamine ions [Ag(NH3)2]+ with D-glucose in the presence of a stabilizing agent. Along with the nature of the dispersing agent, the pH and the temperature of the reaction had the most pronounced effect on the reduction rate, the nucleation of the metallic phase, and ultimately the size and dispersion of the resulting particles. Through suitable manipulations of these parameters, it was possible to prepare uniform Ag nanoparticles ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 41 publications
12
57
0
Order By: Relevance
“…At alkaline condition, large numbers of nanoparticles with smaller diameters were formed since large numbers of functional groups were available for silver binding. This result confirmed the important role played by pH in controlling the shape and size of Ag nanoparticle synthesis, as reported in [42] with similar pH effect.…”
Section: Resultssupporting
confidence: 90%
“…At alkaline condition, large numbers of nanoparticles with smaller diameters were formed since large numbers of functional groups were available for silver binding. This result confirmed the important role played by pH in controlling the shape and size of Ag nanoparticle synthesis, as reported in [42] with similar pH effect.…”
Section: Resultssupporting
confidence: 90%
“…The investigation reveals that the pH played an important role in controlling the size of the silver nanoparticles. A similar pH effect was reported at elevated pH in addition to the complete and rapid reduction of the silver nanoparticles 39 .…”
Section: Effect Of Ph On Thesupporting
confidence: 75%
“…Earlier reports indicated that the pH of a reaction mixture greatly influenced the biosynthesis of NPs as well as their stability. According to Andreescu et al [25], an increase in the pH resulted in an increase in the absolute value of the negative zeta potential, which led to the formation of highly stable NPs. This phenomenon could be attributed to electrostatic repulsions at high pH or the high absolute value of the negative zeta potential [26].…”
Section: Reaction Phmentioning
confidence: 99%